Analysis of Land Availability For The Pasangkayu District Transmigration Program - Gunawan; Ahmad Munir; Andang Surya Soma (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
Transmigration is one of the government's efforts to achieve a balance in population distribution, expand job opportunities, increase production, and boost income. The development of the Transmigration Area Technical Plan for Settlement Units Tanjung Cina is intended to optimize natural resources and the strategic potential of other regions. This research was conducted to assess the suitability of the transmigration settlement land in Technical Plan for Settlement Units Tanjung Cina in Bambakoro Village, Pasangkayu Regency. To meet the data needs of this research, data collection was carried out on the objects to be studied to obtain an overview of data or information about the research area. The data consists of primary and secondary data obtained from survey methods. The research results indicate the physical factors influencing the land suitability for transmigration land in Technical Plan for Settlement Units Tanjung Cina in Bambakoro Village. The suitability of transmigration settlement land in Technical Plan for Settlement Units Tanjung Cina in Bambakoro Village, Pasangkayu Regency, shows favorable results. Furthermore, the development of Transmigration RTSP Tanjung Cina has a significant impact on the welfare of the people and the progress of the region.